Strategi Pengembangan Usaha Ternak Tikus (Rattus norvegicus) dan Mencit (Mus musculus) di Fakultas Peternakan IPB - Kartika, A. A.; Hotnida, H. C. H.; Fuah, A. M. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2013)
This research aimed to formulate development strategies for white rat and mice enterprise. The data were obtained using questionnaire and interview thenthe strategies were analyzed using internal factor evaluation (IFE), external factor evaluation(EFE), internal-external matrix(IE), SWOT, and QSPM analysis. IFE analysis showed that the company was in fairly good condition (IFE score: 2.5602) including the managementusing standard operational procedure (SOP) that comprise breeding system, cage hygiene, waste management and marketing. EFE matrix analysis showed that the company could use the opportunity (“high demand” and “cooperation with research institutions and reptiles breeders”) eventhough there was a threat (“high production cost due to increased fuel costs”) (EFEScore: 3.0353). IE matrix showed that the rat and mice farm of Aneka Ternak laboratory was in “growth and build” position and the right strategy is intensive or integration strategy. Alternative strategies were formulated using SWOT matrix and its priority was set by QSPM analysis. QSPM analysis showed that the prioritystrategyneeded was to establish more partnerships with research institutions and reptiles breeders to improve marketing channels (TAS Score: 18.5633).